Single cultivation versus sweet potato and popcorn intercropping: benefits over edaphic fauna in ecological-based system - Redin, Marciel; Canepelle, Eduardo; Carlson Writzl, Thaniel; da Silva, Danni Maisa; Guerra, Divanilde; Drescher, Marta Sandra (Revista Ceres, 2025)
The objective of this study was to evaluate the diversity and abundance of edaphic fauna organisms in single and intercropped systems of sweet potato (Ipomoea batatas) and ecologically-based popcorn (Zea mays) in Red Oxisol, in the Northwest region of the state of Rio Grande do Sul, Brazil. Four sweet potato cultivars were used in single systems and intercropped with popcorn: BRS Amélia, BRS Rubissol, BRS Cuia and Crioula. The soil fauna assessment was carried out using PROVID-type traps. Richness, abundance and the dominance indices of Shannon (H’) and Simpson (D) were determined. The orders Coleoptera, Hymenoptera, Collembola and Orthoptera, were dominant in both cultivation systems. The single cultivation showed a greater number of organisms in the orders Isopoda and Collembola, whereas in the intercropped system, the orders Lepidoptera and Hymenoptera stood out. The intercropping cultivation of sweet potato and popcorn shows highest diversity and abundance of soil organisms compared to the single cultivation.